Development of Busy Book Learning Media to Increase Interest in Learning Islamic Religious Education in Grade IV Elementary School Students - Alsufi, Alsufi; K, Nurdin; Arifuddin, Arifuddin; Junaid, Hapsa (South Sulawesi Education Development (SSED), 2025)
This study aims to develop busy book learning media to increase interest in learning Islamic Religious Education in grade IV students. The method used is R&D with the ADDIE model. The subjects of the study consisted of 20 students and one teacher. Data were collected through observation, questionnaires, interviews, and documentation. The results show that this media is valid (media experts 82%, material experts 99%), practical (student responses 90%, teachers 98%), and effective (N-Gain score 0.8 or 87%). Busy books are declared valid, practical, and effective in increasing interest in learning Islamic Religious Education.